Circ_0099630 Participates in SPRY1-Mediated Repression in Periodontitis - Jing Wang; Zhenning Wang; Meng Huang; Yu Zhang; Lulu Xu (Elsevier, 2023)
Background: Periodontitis is chronic inflammation that causes damage to periodontal tissues and cementum. It has been reported that circular RNA hsa_circ_0099630 (circ_0099630) was overexpressed in gingival samples from patients with periodontitis. However, the function of circ_0099630 on the osteogenic differentiation of periodontal ligament cells (PDLCs) in periodontitis remains unclear. Methods: Periodontal ligaments from patients with periodontitis and third molars (termed wisdom teeth) were utilised to isolate inflamed PDLCs (iPDLCs) and healthy PDLCs (hPDLCs). Expression levels of circ_0099630 in isolated PDLCs were assessed using reverse transcription quantitative polymerase chain reaction (RT-qPCR). Effects of circ_0099630 overexpression and silencing on iPDLC viability, proliferation, and cycle progression were determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), 5-ethynyl-2'-deoxyuridine (EdU), and flow cytometry assays. The osteogenic differentiation was detected by analysing the alkaline phosphatase (ALP) activity, mineralisation amount, and osteogenic markers osterix (OSX), ALP, and RUNX2 in iPDLCs. The regulatory mechanism of circ_0099630 was predicted by bioinformatics analysis and validated by dual-luciferase reporter, RNA immunoprecipitation, and RNA pull-down assays. Results: Circ_0099630 was underexpressed in iPDLCs compared to hPDLCs. Overexpression of circ_0099630 repressed iPDLC proliferation and osteogenic differentiation, but circ_0099630 silencing exerted an opposing effect. Mechanically, circ_0099630 sponged miR-212-5p to block the inhibiting effect of miR-212-5p on SPRY1. Elevated expression of SPRY1 partly reversed the promoting effect of circ_0099630 knockdown on iPDLC proliferation and osteogenic differentiation. Conclusions: Circ_0099630 curbed PDLC proliferation and osteogenic differentiation through elevating SPRY1 expression via sponging miR-212-5p in periodontitis.